Bifunctional free radical photoinitiator based on syringaldehyde. (22nd January 2022) - Li, Qianmin; Li, Huimin; Wang, Zhen; Liu, Jiuhong; Chen, Xuquan; Liu, Dayong; Song, Liang; Han, Yuxi; Wang, Zhongwei; Yu, Qing
Abstract: Syringaldehyde, a natural compound, was chosen to design a novel acylphosphine oxide (S1). Maximum absorption at 337 nm with very high molar extinction coefficient (above 13, 000 M −1  cm −1 ) was detected for S1. As a type I photoinitiator, S1 could initiate the photopolymerization of TMPTA and ca. 50% of the double bond conversion (DC) could be obtained upon irradiation of LED@385 nm or LED@420 nm for 300 s. As coinitiator in type II system, S1 could cooperate with DETX and exhibit higher performance (ca. 60% of DC) than typical pair of DETX and EDAB. Density functional theory (DFT) is used to study the characteristics of excited state and transition manners of S1 after light absorption. Orbital distributions of singlet and triplet electron clouds, transition energy levels, and oscillator strength are also predicted. Results suggest that after intersystem crossing (ISC) and internal conversion (IC), free radicals formed through α‐cleavage (Norrish Type I reaction) or breakage of O‐H bond in S1. All results indicate that S1 could act as a bifunctional photoinitiator. Based on the above results, the roles of S1 during photoinitiation are also proposed.